Attitudes of women to fetal tissue research. Issue 1 (March 1994) - Anderson, F; Glasier, A; Ross, J; Baird, D T
Abstract : The use of human fetal tissue for scientific research has enormous potential but is subject to government legislation. In the United Kingdom the Polkinghorne Committee's guidelines were accepted by the Department of Health in 1990. These guidelines set out to protect women undergoing termination of pregnancy from exploitation but in so doing may significantly restrict potential research. Although the committee took evidence from a wide variety of experts they did not seek the views of the general public. We asked 108 women about to have a therapeutic abortion; 167 women who had had a pregnancy terminated in the past, and 419 women who had never had an abortion, their views on research using human fetal tissue. Regardless of their past experiences the women were overwhelmingly in favour of research using fetal tissue (94 per cent). They made little distinction between basic research and research with obvious clinical relevance and supported the concept of using transplanted fetal tissue for the treatment of adult disease such as Parkinsonism. Women about to undergo an abortion were significantly more likely (p < 0.001) to approve of all types of research including that aimed at improving methods of abortion and research using live fetuses in utero.